2020
DOI: 10.1016/j.ultrasmedbio.2019.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Use of 3-D Contrast-Enhanced Ultrasound to Evaluate Tumor Microvasculature After Nanoparticle-Mediated Modulation

Abstract: A cost-effective method for serial in vivo imaging of tumor microvasculature has been developed.We evaluated acoustic angiography (AA) for visualizing and assessing non-small cell lung tumor (A549) microvasculature in mice prior to and following tumor vascular disruption by vasculartargeted gold nanoparticles (GNPs) and radiotherapy. Standard B-mode and microbubbleenhanced AA images were acquired at pre-and post-treatment time points. Using these modes, a new metric, 50% Vessel Penetration Depth (VPD 50 ) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Here we have shown that although the underlying mechanism of treatment is still vascular disruption, overall tumor growth was still hindered compared to control treatment and long term hypoxia was prevented. This transient vascular disruption was further confirmed by Kwon et al demonstrating an increase in microbubble perfusion 24 hours post therapy followed by normalization to baseline levels, indicative of normalization of tumor vasculature flow [55].…”
Section: Plos Onementioning
confidence: 53%
“…Here we have shown that although the underlying mechanism of treatment is still vascular disruption, overall tumor growth was still hindered compared to control treatment and long term hypoxia was prevented. This transient vascular disruption was further confirmed by Kwon et al demonstrating an increase in microbubble perfusion 24 hours post therapy followed by normalization to baseline levels, indicative of normalization of tumor vasculature flow [55].…”
Section: Plos Onementioning
confidence: 53%
“…Vascular flow is important because the volume of the tumor is small, and it is essential for rapid growth; therefore, tumors that achieve more angiogenesis may grow faster (37). In a study quantifying tumor perfusion by acoustic angiography, was observed that an animal of the untreated control group had small tumor growth and exhibited poor perfusion within the tumor compared to the other animals of the same group (39). In contrast, when we analyze the evolution of VI over time, we observe that the FG group has a higher initial VI but tends to decrease over time.…”
Section: Discussionmentioning
confidence: 99%